Tuning properties of mid-infrared Fabry-Pérot quantum cascade lasers for multiheterodyne spectroscopy - Sterczewski, Lukasz Antoni; Westberg, Jonas; Wysocki, Gerard (Photonics Letters of Poland, 2016)
Injection current tuning properties of an 8.5 um Fabry-Pérot mid-infrared quantum cascade laser are evaluated by analyzing the mode-by-mode frequency tuning behavior with an identification of high-noise regimes in a delayed self-heterodyne experiment. We find that modes on the edges of the spectral envelope exhibit anomalous tuning coefficients compared to those in the center. Furthermore, the frequencies of individual modes are susceptible to parasitic etalons, likely causing laser frequency pulling. Despite the complicated tuning behavior, low phase-noise operating regimes exist, and are compatible with high resolution multiheterodyne spectroscopy of gases. Full Text: PDF References J. Faist, F. Capasso, D.L. Sivco, C. Sirtori, A.L. Hutchinson, A.Y. Cho, "Quantum Cascade Laser", Science 264 (1994) 553?556. CrossRef A. Hugi, G. Villares, S. Blaser, H.C. Liu, J. Faist, "Mid-infrared frequency comb based on a quantum cascade laser", Nature 492 (2012) 229?233. CrossRef G. Villares, A. Hugi, S. Blaser, J. Faist,"Dual-comb spectroscopy based on quantum-cascade-laser frequency combs", Nat. Commun. 5 (2014) 5192. CrossRef G. Villares, S. Riedi, J. Wolf, D. Kazakov, M.J. Süess, P. Jouy, M. Beck, J. Faist, "Dispersion engineering of quantum cascade laser frequency combs", Optica 3 (2016) 252. CrossRef Y. Wang, M.G. Soskind, W. Wang, G. Wysocki, "High-resolution multi-heterodyne spectroscopy based on Fabry-Perot quantum cascade lasers", Appl. Phys. Lett. 104 (2014) 31114. CrossRef A. Hangauer, J. Westberg, E. Zhang, G. Wysocki, "Wavelength modulated multiheterodyne spectroscopy using Fabry-Pérot quantum cascade lasers", Opt. Express 24 (2016) 25298. CrossRef D. Burghoff, Y. Yang, D.J. Hayton, J.-R. Gao, J.L. Reno, Q. Hu, "Evaluating the coherence and time-domain profile of quantum cascade laser frequency combs", Opt. Express 23 (2015) 1190?1202. CrossRef A. Gordon, C.Y. Wang, L. Diehl, F.X. Kärtner, A. Belyanin, D. Bour, S. Corzine, G. Höfler, H.C. Liu, H. Schneider, T. Maier, M. Troccoli, J. Faist, F. Capasso, "Multimode regimes in quantum cascade lasers: From coherent instabilities to spatial hole burning", Phys. Rev. A 77 (2008). CrossRef S. Blaser, D.A. Yarekha, L. Hvozdara, Y. Bonetti, A. Muller, M. Giovannini, J. Faist, "Room-temperature, continuous-wave, single-mode quantum-cascade lasers at ?=5.4?m", Appl. Phys. Lett. 86 (2005) 41109. CrossRef S. Schiller, "Spectrometry with frequency combs", Opt. Lett. 27 (2002) 766?768. CrossRef T. Tsai, G. Wysocki, "Active wavelength control of an external cavity quantum cascade laser", Appl. Phys. B Lasers Opt. 109 (2012) 415?421. CrossRef